Group Interpersonal Psychotherapy in Patients with Treatment Resistant Depression: A Qualitative Analysis - Maria Isabel Perez Mattos; Daniela Knauth; Anna Viduani; Scott Stuart; Bruno Paz Mosqueiro; Marco Antonio Caldieraro; Laura Wolf de Souza; Ariane Gusmão Chini; Rachel Santos Nery; Manoella Pestana Lopes; Marcelo P. Fleck (SAGE Open)
Depressive disorders are a worldwide leading cause of health-related burden, and a subgroup of depression patients fail to respond to available psychopharmacological treatments, a condition called Treatment Resistant Depression (TRD). While evidence suggests that both traditional and group (IPT-G) Interpersonal Psychotherapy interventions are efficient treatments for depression, few studies have evaluated the effect of IPT on TRD. Qualitatively analyze an IPT-G intervention conducted with TRD patients using a deductive, theory informed approach, to explore how TDR patients understand, contextualize and apply IPT’s problem-areas throughout the course of the treatment. 10 IPT-G sessions were analyzed using Framework Analysis. Sessions were video recorded and transcribed verbatim, and participants’ accounts were coded with predetermined, conceptually derived codes that were based on the three main problem areas identified in IPT. Following IPT’s main problem areas, three themes were generated: “Mechanisms of change—Improving communication”; “Acceptance of loss”; and “Finding new roles—depression, role transition, and reclaiming life conditions.” Our analysis suggests that patients with TRD can benefit from IPT-G. Depression is seen as a chronic condition that deeply affects the lives of patients, and IPT-G was seen as a way of promoting change and regaining control. However, we identified that patients to whom IPT-G did not achieve the same effect in terms of symptom reduction have greater difficulty in acquiring and generalizing new interpersonal skills, and often were immersed in severe family or marital interpersonal disputes.